DEVELOPING A MODEL OF TEACHING READING COMPREHENSION FOR EFL STUDENTS - Arifuddin Hamra; Enny Syatriana (TEFLIN, 2010)
Abstract: This study aimed at designing a model of teaching reading comprehension based on the objectives of teaching reading at the senior high school and the teachersâ understanding of the school curriculum and to describe the implementation of the model. The subject consisted of 24 teachers, 167 students of five SMAs (senior high schools) in South Sulawesi, Indonesia. This developmental study had five steps: analysis, design, development, implementation, and evaluation. The result indicates that the model significantly increases the reading comprehension of EFL students (M = -14.43114), t (166) = -16.155, p